The Holy Trinity and the Human Person - Зизијулас, Јован Д. (Sabornost - The Theological Year-book, 2016)
The author examines the relationship between Christian Trinitarian theology and anthropology. The essence of the anthropology which results from the Trinitarian theology of the Cappadocian Fathers lies in the significance of personhood in human existence. There is no fuller anthropology than this anthropology of true and full personhood, where the concept of the person is an ontological concept in the ultimate sense.